91 Floor Space Allocation Effects on Heavy Weight Finishing Pigs (over 135 kg). (10th April 2018) - Samuel, R; Thaler, B C; Levesque, C L; Darrington, J
Abstract: Finishing pigs are stocked to maximize floor space utilization, in accordance with the designed number of animals per pen. However, because currently available floor space allocation recommendations are based on considerably lighter market weight pigs, it raises the question of whether these recommendations require revision. The objective of this study was to investigate the effects of individual floor space allocation on feed conversion and overall performance of pigs from 105.2 ± 0.5 kg to heavy weight finishers over 135 kg. Pigs were provided free access to water via two cup waters and meal diets from 173 cm of linear feeder space in each pen throughout the trial. Diets were based on corn and soybean meal and formulated to meet or exceed nutrient requirements (NRC, 2012) in two phases: 1) 100 to 120 kg providing 0.57% SID lysine and 2) 120 to 140 kg providing 0.48% SID lysine. Three floor space per pig allocations were tested: 0.88, 0.75, and 0.61 m 2 /pig. The standard gate position provided 0.88 m 2 /pig; all pens were stocked with 23 pigs per pen to begin the trial. All removals and treatments were documented. Pen weights were measured using a pen scale every week. Feed remaining was quantified by measuring the feed in the feeders before weighing the pens each period. Pigs were marketed when the average weight of pigs in the barn reached 135 kg. The heaviest 5 pigs from each pen were marketed in a first and a second cut one week apart before the remaining pigs were marketed in the third week. Data was analyzed as a randomized complete block design. Overall, feed disappearance per pig was not affected by floor space allocation ( P > 0.49). Similarly, the mean body weights of pigs were not different between treatments at the beginning of the trial ( P = 0.89) or any subsequent period ( P > 0.15). As a result, feed conversion efficiency was not changed by the pen space treatments ( P > 0.10). Marketing was balanced between treatments, which resulted in pigs raised with 0.61 m 2 /pig tending ( P < 0.09) to be lighter at marketing in the first and second cut than those raised with 0.88 m 2 /pig. However, there was no difference in body weight between the floor space allocations when the final group was marketed (143.3 ± 0.6 kg; P = 0.42). Carcass lean percent tended ( P = 0.08) to be greater (56.8 vs. 56.4 %) from pigs provided 0.61 m 2 /pig of floor space, thus improving ( P = 0.03) the carcass value (60.52 vs. 59.71/cwt) of those animals compared to pigs provided 0.88 m 2 /pig. Immediately before marketing the heaviest finisher pigs, reduced floor space allocation negatively impacted the final body weight of animals.